Association Of Serum Magnesium Level with and Without Retinopathy in Type-2 Diabetes Mellitus - Vineela, R.H.P.V.; S. V, Srinivasa.; Lokesh. M, Lokesh. M (Journal of Neonatal Surgery, 2025)
Background: Diabetes mellitus (DM) is a metabolic disorder which occurs due to a complex interaction between environmental, genetic and lifestyle factors. Hyperglycemia due to DM leads to microvascular and macrovascular complications. Diabetic retinopathy (DR) is an important cause of vision impairment and blindness among the working adult population. Vascular proliferation and maculopathy observed in this disease may be controlled by adequate glycemic management and prompt ocular intervention. Magnesium is known to play an essential role in both insulin release and cellular glucose metabolism. Hypomagnesemia is seen in diabetics due to increased urinary loss and decreased dietary intake and absorption. Insulin causes shift of magnesium from extracellular to intracellular Materials And Methods:Cross sectional study  Study Design: Cross-sectional observational study  Study period: 3 months  Sample size: 60  Study area: R. L. Jalappa Hospital  Study population: patients >40 years age with type 2 DM, serum creatinine ⩽1.2 mg/dL and without microalbuminuria Results The age of the study population varied between 40-68 years. Male patients were 68% and female patients were 32% of the study population. Of the 60 patients studied most of them have diabetic retinopathy changes. Majority of the patients with retinopathy had NPDR changes rather than PDR. Serum magnesium levels in patients with retinopathy was lower compared to those without retinopathy. Serum magnesium levels are inversely proportional to severity of retinopathy in patients with retinopathy Conclusion  Serum magnesium levels were low in patients with diabetic retinopathy.  Patients with Sight threatening diabetic retinopathy (STDR) had relatively lower serum magnesium levels compared to those without STDR.